Gradients of Orientation, Composition, and Hydration of Proteins for Efficient Light Collection by the Cornea of the Horseshoe Crab - Spaeker, Oliver; Taylor, Gavin J; Wilts, Bodo D; Slabý, Tomáš; Abdel-Rahman, Mohamed Ashraf Khalil; Scoppola, Ernesto; Schmitt, Clemens N Z; Sztucki, Michael; Liu, Jiliang; Bertinetti, Luca; Wagermaier, Wolfgang; Scholtz, Gerhard; et al. (Advanced science (Weinheim, Baden-Wurttemberg, Germany), 2022)
The lateral eyes of the horseshoe crab, Limulus polyphemus, are the largest compound eyes within recent Arthropoda. The cornea of these eyes contains hundreds of inward projecting elongated cuticular cones and concentrate light onto proximal photoreceptor cells. Although this visual system has been extensively studied before, the precise mechanism allowing vision has remained controversial. Correlating high-resolution quantitative refractive index (RI) mapping and structural analysis, it is demonstrated how gradients of RI in the cornea stem from structural and compositional gradients in the cornea. In particular, these RI variations result from the chitin-protein fibers architecture, heterogeneity in protein composition, and bromine doping, as well as spatial variation in water content resulting from matrix cross-linking on the one hand and cuticle porosity on the other hand. Combining the realistic cornea structure and measured RI gradients with full-wave optical modeling and ray tracing, it is revealed that the light collection mechanism switches from refraction-based graded index (GRIN) optics at normal light incidence to combined GRIN and total internal reflection mechanism at high incident angles. The optical properties of the cornea are governed by different mechanisms at different hierarchical levels, demonstrating the remarkable versatility of arthropod cuticle.
Keywords: Animals; Horseshoe Crabs; zrak; ostrorepi; biomaterials; rohovka; vision; structure-function relationships; Cornea; Photoreceptor Cells; Proteins; chitin-based materials; proteiny; optical materials; optical modeling; zvířata; protein composition; fotoreceptory; Vision, Ocular